(untitled) (Innovation & Development in Engineering and Applied Science, 2023)
Health and safety management in small and medium-sized companies (SMEs) is very deficient because they have fewer resources than large companies, which affects the low prevention of occupational risks. The research objective was to know the importance and use of health and safety management standards in SMEs to prevent occupational hazards. For this, a systematic review of 24 scientific articles in English and Spanish was carried out with a descriptive and exploratory scope. In summary, few studies in SMEs on health and safety management systems, as well as ISO standards, are used, and the evaluation of these management systems is specific for each type of activity. Reasons why developing management standards adapted to the reality of these organizations is essential.